The last crusade in the West : Castile and the conquest of Granada - O'Callaghan, Joseph F. (Middle Ages series., 2014)
The Last Crusade in the West traces Castilian efforts to conquer Granada from the middle of the fourteenth century until the end of the fifteenth. Although the Castilian kings neglected the reconquest for many years, Fernando and Isabel achieved the capitulation of Granada in 1492.